Provenance of a Late Permian retroarc foreland basin along the eastern Gondwanan margin: northern Sydney Basin, eastern Australia - Maravelis, Angelos G.; Offler, Robin; Botziolis, Chrysanthos; Pantopoulos, George; Scott, Alexandra; Landenberger, Bill; Collins, William J. (Geological magazine, 2023)
The Upper Permian sedimentary successions in the northern Sydney Basin have been the subject of several stratigraphic, sedimentological and coal petrographic studies, and recently, extensive U-Pb zircon dating has been carried out on tuffs in the Newcastle Coal Measures. However, detailed petrographic and geochemical studies of these successions are lacking. These are important because a major change in tectonic setting occurred prior to the Late Permian because of the Hunter-Bowen Orogeny that caused the uplift of the Carboniferous and Devonian successions in the Tamworth Group and Tablelands Complex adjacent to the Sydney Basin. This should be reflected in the detrital makeup of the Upper Permian rocks. This study provides data that confirms major changes did take place at this time. Petrographic analysis indicates that the source area is composed of sedimentary, felsic volcanic and plutonic and low-grade metamorphic rocks. Conglomerate clast composition analysis confirms these results, revealing a source region that is composed of felsic volcanics, cherts, mudstones and sandstones. Geochemical analysis suggests that the sediments are geochemically mature and have undergone a moderate degree of weathering. The provenance data presented in this paper indicate that the southern New England Orogen is the principal source of detritus in the basin. Discrimination diagrams confirm that the source rocks derive from an arc-related, contractional setting and agree with the provenance analyses that indicate sediment deposition in a retroarc foreland basin. This study offers new insights on the provenance and tectonic setting of the Northern Sydney Basin, eastern Australia.